Implementing School Religious Culture Program to Develop Early Childhood’s Noble Character at TKN Pembina Wlingi - Tri Hidayati; Ahmad Samawi; Ahmad Yusuf Sobri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research addresses the critical need to implement the School Religious Culture program during early childhood to cultivate noble character through daily activities.The study utilized a qualitative approach at TKN Pembina Wlingi through interviews, observation, and documentation, focusing on: (1) program implementation, (2) supporting and inhibiting factors, and (3) strategies for factor management.The findings confirm that the School Religious Culture program successfully develops the noble character of early childhood children, producing individuals who are more positive, religious, and morally upright. This success is strongly supported by the principal, teachers, educational staff, and parents, who continuously strive to instill religious character through consistent, non-pressurized daily habituation.